2015
DOI: 10.1007/s00338-015-1337-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in spawning time led to the speciation of the broadcast spawning corals Acropora digitifera and the cryptic species Acropora sp. 1 with similar gamete recognition systems

Abstract: Multi-species spawning is reported in the coral genus Acropora, but hybridization in nature rarely occurs because of the incompatibility of gametes and the timing of spawning. However, the evolutionary relationships between gamete compatibility and spawning time are obscure. Investigations of gamete compatibility in sister species that spawn at different times may provide clues to answering this question. Acropora sp. 1 has been defined as a cryptic species of Acropora digitifera, and they are morphologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…The spawning timetable of A. digitifera at Sesoko Island in the present study and in Ohki et al (2015) correlates with previous reports on Acropora spawning in Japan: from 3 d before to 10 d after the full moon (see Fujiwara et al 2015, Mezaki 2016. Ohki et al (2015) reported that spawning of A. digitifera occurred on several days around the full moon of June, 2013 at the same locality as our study.…”
Section: Recording Of Acropora Digitifera Spawning By Continuous Intesupporting
confidence: 80%
See 2 more Smart Citations
“…The spawning timetable of A. digitifera at Sesoko Island in the present study and in Ohki et al (2015) correlates with previous reports on Acropora spawning in Japan: from 3 d before to 10 d after the full moon (see Fujiwara et al 2015, Mezaki 2016. Ohki et al (2015) reported that spawning of A. digitifera occurred on several days around the full moon of June, 2013 at the same locality as our study.…”
Section: Recording Of Acropora Digitifera Spawning By Continuous Intesupporting
confidence: 80%
“…Ohki et al (2015) reported that spawning of A. digitifera occurred on several days around the full moon of June, 2013 at the same locality as our study. They observed the setting of gamete bundles at 20:30 hours to 21:00 hours to determine whether spawning had taken place.…”
Section: Recording Of Acropora Digitifera Spawning By Continuous Intementioning
confidence: 48%
See 1 more Smart Citation
“…The octocoral species, Heliopora coerulea, is also separated into two genetic clusters that are related to branch morphotype (Yasuda et al 2014). Compared with G. fascicularis, these Acropora and Heliopora species are influenced by the difference in temporal reproductive isolation (Acropora: Hayashibara and Shimoike 2002;Ohki et al 2015;Heliopora: Villanueva 2015).…”
Section: Interbreeding and Ambiguous Mitochondrial Typementioning
confidence: 99%
“…Acropora is the most speciose genus of hard corals, with 134 species [19] organized into 19 species groups based on skeletal similarities [20]. To date, molecular phylogenetic studies of Acropora have focused on the mitochondrial DNA Control Region (CR) and the nuclear PaxC intron [11,[21][22][23][24][25][26] (hereafter referred to as PaxC), which have produced significantly different phylogenies [11,22,27]. Incongruence between these regions has been attributed primarily to introgressive hybridization [11,22,23,27], but recent evidence suggests that PaxC is under selection and is associated with differences in spawning time, owing to two highly diverged PaxC lineages (F ST ¼ 0.98) that are correlated with different seasonal spawning cohorts in A. samoensis and A. tenuis [17,28].…”
Section: Introductionmentioning
confidence: 99%